Dual-Tracer Assessment of Dynamic Changes in Reoxygenation and Proliferation Decrease During Fractionated Radiotherapy in Murine Tumors - Yu, Wenjing; Su, Xiaoyu; Zhang, Dan; Qiao, Feng; Wang, Hui; Jiang, Jinhui; Xu, Huiqin (Frontiers in Oncology, 2020)
Objective: The present work aimed to assess reoxygenation and tumor inhibition during fractionated radiotherapy (FRT) in murine tumors using 18F-fluoromisonidazole (18F-FMISO) and 18F-fluorothymidine (18F-FLT) based micro positron emission tomography/computed tomography (PET/CT). Materials and Methods: A nude mouse xenograft model was established with the head and neck squamous carcinoma cell (FaDu), followed by administration of FRT. Imaging was carried out with both 18F-FMISO and 18F-FLT PET/CT, prior to FRT (Pre-FRT, 0 Gy), during FRT (Inter-FRT, 21 Gy), and after FRT (Post-FRT, 40 Gy). The maximum standardized uptake (SUVmax) and tumor-to-normal muscle ratio (TNR) were determined in regions of interest (ROIs) in 18F-FMISO and 18F-FLT PET/CT images. Then, hypoxic (HV) and proliferative tumor (PTV) volumes obtained by PET/CT were analyzed. Immunohistochemistry was performed to analyze the changes of hypoxia-inducible factor- (HIF)-1α, carbonic anhydrase 9 (CAIX), Ki67 and proliferating cell nuclear antigen (PCNA). Associations of the levels of these biomarkers with PET/CT parameters were analyzed. Results:18F-FMISO PET/CT demonstrated markedly elevated reduction rates of SUVmax (30.3 vs. 14.5%, p = 0.012), TNR (27.9 vs. 18.3%, p = 0.032) and HV (85.0 vs. 71.4%, p = 0.047) from Pre-FRT to Inter-FRT compared with values from Inter-FRT to Post-FRT. Meanwhile, PTV reduction rate in 18F-FLT PET/CT from Pre-FRT to Inter-FRT was significantly decreased compared with that from Inter-FRT to Post-FRT (21.2 vs. 82.7%, p = 0.012). Tumor HIF-1α, CAIX, Ki67, and PCNA amounts were continuously down-regulated during radiotherapy. TNR (FMISO) showed significant correlations with HIF-1α (r = 0.692, p = 0.015) and CAIX (r = 0.801, p = 0.006) amounts in xenografts, while associations of SUVmax (FMISO) with hypoxia markers were weak (r = 0.418, p = 0.041 and r = 0.389, p = 0.037, respectively). SUVmax (FLT) was significantly correlated with Ki67 (r = 0.792, p = 0.003) and PCNA (r = 0.837, p = 0.004). Conclusions: Tumor reoxygenation occurs early during radiotherapy, while inhibition of cell proliferation by tumoricidal effects mainly takes place gradually with the course of radiotherapy. 18F-FMISO and 18F-FLT PET/CT are sensitive and non-invasive tools for the monitoring of tumor reoxygenation and proliferation during radiotherapy.